MA'HAD ALY LIBRARY ENTREPRENEURIAL MANAGEMENT STRATEGY TO SUPPORT THE FINANCIAL EFFICIENCY OF ISLAMIC EDUCATION - Julia Iqna’a, Faiq; Abdullah (International Journal of Multidisciplinary Reseach, 2025)
This study focuses on the entrepreneurial management strategy of the Rabi' bin Sulaiman Ma'had Aly Nurul Jadid Library in supporting the financial efficiency of Islamic education. The study aimed to understand how the library manages business units such as printing services, book cover services, and book sales, so that it can cover operational costs and support the procurement of additional facilities without always relying on funds from the parent institution. This study used a qualitative method with a case study approach, involving four purposive informants: the head of the library, staff, treasurer, and students. Data collection techniques included in-depth interviews, participant observation, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive analysis model, encompassing data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the library's entrepreneurial strategy can increase the institution's financial efficiency, improve service quality, and support the procurement of physical facilities such as cabinets and other supporting equipment. This approach confirms that libraries can act as independent units that not only serve academic needs but also make significant contributions to the institution's financial sustainability. The implications of this study highlight the importance of developing an entrepreneurial strategy based on needs analysis, systematic operational management, and transparent financial record-keeping as a model that can be implemented by other libraries in Islamic education settings and academic institutions in general.